Agrarian change and mobilisation (New Delhi, 2012)
The articles in this volume compose a panoramic view of the kinds of changes that have been taking place in agrarian structures and their underlying effects on the other aspects of rural life. They discuss the themes of changes, continuities and challenges in the theoretical perspectives and methodological approaches in critical agrarian change.
Keywords: Agrarian change